Collagen synthesis on ultravioletA irradiated human skin fibroblast treated with insulin - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Ultraviolet (UV) irradiation from the sun can stimulate premature skin aging because UV irradiation inhibits collagen synthesis, promotes collagen degradation and inhibits fibroblast proliferation. Insulin is capable to stimulate fibroblast genes collagen expression, DNAsynthesis, and collagen synthesis. The effect of insulin in reducing collagen synthesis among repeated-UV A irradiation on human skin fibroblast has never been studied. This study aims to investigate the effect of insulin in collagen synthesis among repeated-UVA irradiation on normal human skin fibroblast. To asses the collagen synthesis collagen degradation, collagen deposition and fibroblast proliferation were measured. Experimental study was performed among passage 3 of fibroblast which was isolated from a circumcised skin of a 6-year-old boy. Fibroblasts were irradiated with 3 repeated exposure with total cumulative dose 9000 mJ/cm' and treated with insulin 0.5